Evaluating customer perspectives on omnichannel shopping satisfaction in the fashion retail sector - Khalid, Bilal (My University, 2024)
The effective implementation of omnichannel commerce can fundamentally alter how consumers shop online. This study attempted to understand Thai consumers' omnichannel fashion retail purchasing activities. The objectives of the study were to investigate the determinants shaping omnichannel customer experiences within the fashion retail industry and to examine the impact of omnichannel customer experiences on customer satisfaction within the Thai retail industry. The research utilized the Unified Theory of Acceptance and Use of Technology (UTAUT) model to analyze the effects of omnichannels on purchasing behaviors and levels of satisfaction of consumers. The study employed a survey research design, applying simple random sampling to select 509 respondents with omnichannel shopping experience in the clothing and fashion. The respondent data was analyzed using structural equation modeling utilizing the Amos software version 24. Analyzing the results revealed a significant correlation between omnichannel shopping and customer satisfaction in fashion retail shopping. Perceived ease of use, perceived enjoyment, integrated promotions, integrated customer service, and integrated transactions were all found to influence omnichannel experiences favorably. The findings suggest that fashion retailers prioritize customer satisfaction by enhancing their omnichannel experiences through better coordination and synchronization of their different customer service channels.
Keywords: And integrated transactions; Customers perspective; Integrated customer service; Integrated promotions; Omnichannel